New user? Sign up

Existing user? Log in

Can anyone tell me how to calculate general sum of sequence till \(n\) . \[1^{4}+2^{4}+3^{4}+ \ldots +n^{4}\]

Note by Akshat Sharda 3 years, 9 months ago

Easy Math Editor

*italics*

_italics_

**bold**

__bold__

- bulleted- list

1. numbered2. list

paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)

> This is a quote

This is a quote

# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"

2 \times 3

2^{34}

a_{i-1}

\frac{2}{3}

\sqrt{2}

\sum_{i=1}^3

\sin \theta

\boxed{123}

Sort by:

Hint:

\[ \begin{eqnarray} \sum_{k=1}^n \left( (k+1)^2 - k^2 \right) &= &2 \sum_{k=1}^n k + \sum_{k=1}^n 1 \\ \displaystyle (n+1)^2 - 1 &=& 2 \color{blue}{\sum_{k=1}^n k} + n \\ \displaystyle \sum_{k=1}^n k &=& \frac{n(n+1)}2 \end{eqnarray} \]

And

\[ \begin{eqnarray} \sum_{k=1}^n \left( (k+1)^3 - k^3 \right) &= & \sum_{k=1}^n (3k^2 + 3k + 1) \\ \displaystyle (n+1)^3 - 1 &=& 3\color{blue}{ \sum_{k=1}^n k^2} +3 \sum_{k=1}^n k + \sum_{k=1}^n 1 \\ \displaystyle (n+1)^3 - 1 &=& 3\color{blue}{ \sum_{k=1}^n k^2} +3\frac{n(n+1)}2 + n \\ \sum_{k=1}^n k^2 &=& \frac16 n(n+1)(2n+1) \\ \end{eqnarray} \]

Can you find a general pattern to it?

Answer is \( \frac1{30} n(n+1)(2n+1)(3n^2 + 3n-1) \). You can double check your work by induction.

Log in to reply

I appriciate what you did and Thank you for the same.

I have a question- Will this pattern work to find general sum of any power of \(n\)?

Study Bernoulli's Numbers. You'll get the answer for nth power sums. :)

@Satyajit Mohanty – I find that more troublesome, unless you got a table for the number of Bernoulli numbers, then yes, it will be easier, otherwise it takes up more time.

@Pi Han Goh – Well, it's true. I was just giving a general idea! :)

For positive integer powers, yes.

Study Faulhaber's Formula for a General Idea. Also visit Bernoulli's numbers if it interests you. :)

1/30(n+1)(2n+1)(3n^2+3n-1)

(6x + 15x + 10x - x) / 30

Even I know the formula but how to derive it is much more important.

Hm, that simplifies to just \(x\). Are you missing some exponents?

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestHint:\[ \begin{eqnarray} \sum_{k=1}^n \left( (k+1)^2 - k^2 \right) &= &2 \sum_{k=1}^n k + \sum_{k=1}^n 1 \\ \displaystyle (n+1)^2 - 1 &=& 2 \color{blue}{\sum_{k=1}^n k} + n \\ \displaystyle \sum_{k=1}^n k &=& \frac{n(n+1)}2 \end{eqnarray} \]

And

\[ \begin{eqnarray} \sum_{k=1}^n \left( (k+1)^3 - k^3 \right) &= & \sum_{k=1}^n (3k^2 + 3k + 1) \\ \displaystyle (n+1)^3 - 1 &=& 3\color{blue}{ \sum_{k=1}^n k^2} +3 \sum_{k=1}^n k + \sum_{k=1}^n 1 \\ \displaystyle (n+1)^3 - 1 &=& 3\color{blue}{ \sum_{k=1}^n k^2} +3\frac{n(n+1)}2 + n \\ \sum_{k=1}^n k^2 &=& \frac16 n(n+1)(2n+1) \\ \end{eqnarray} \]

Can you find a general pattern to it?

Answer is \( \frac1{30} n(n+1)(2n+1)(3n^2 + 3n-1) \). You can double check your work by induction.

Log in to reply

I appriciate what you did and Thank you for the same.

Log in to reply

I have a question- Will this pattern work to find general sum of any power of \(n\)?

Log in to reply

Study Bernoulli's Numbers. You'll get the answer for nth power sums. :)

Log in to reply

Log in to reply

Log in to reply

For positive integer powers, yes.

Log in to reply

Study Faulhaber's Formula for a General Idea. Also visit Bernoulli's numbers if it interests you. :)

Log in to reply

1/30(n+1)(2n+1)(3n^2+3n-1)

Log in to reply

(6x + 15x + 10x - x) / 30

Log in to reply

Even I know the formula but how to derive it is much more important.

Log in to reply

Hm, that simplifies to just \(x\). Are you missing some exponents?

Log in to reply